Comparison of body composition, bone mineral content and muscle strength variables between elite taekwondo and swimming athletes - Hayrive, C.-A.; Cihan, A.; Bircan, D. (Science, Movement & Health, 2023)
This study aimed to compare the body composition, bone mineral contents, and isokinetic muscle strength variables (maximum strength and muscular endurance) between young elite taekwondo and swimming athletes. Twelve taekwondo athletes (age 16.66±2.46 years, height 167.90±7.89 cm, body mass 57.31±5.63 kg, and BMI 20.34±1.68 kg/m2), and 7 swimmers (age 14.00±1.00 years, height 170.95±5.97 cm, body mass 59.98±7.76 kg, and BMI 20.44±1.53 kg/m2) volunteered to participate in this study. All athletes were well trained and engaged approximately more than 8 years to the specific training (mean training experience: 8.23 ± 1.75 years). The body composition and bone mineral content were evaluated with DXA (Lunar Prodigy Pro; GE, Healthcare, Madison, WI, USA). The concentric isokinetic maximum muscle strength of the knee extensors and flexors was evaluated at angular velocity of 1800/sec for 5 repetitions, and muscular endurance was evaluated at angular velocity of 1800/sec for 30 repetitions using the CSMI-Humac/Norm TM - 770 model (HumacNorm Testing & Rehabilitation System) device. Statistical analysis was done using the Univariate-ANOVA using SPSS-23.0 program, and p<0.05 value was taken as the significance level. The findings of the current study show that the body fat (%) was significantly higher in taekwondo athletes, consequently tissue lean (%) was significantly higher in swimmers (p<0.05). The bone mineral density (g/cm2) was recorded significantly higher in taekwondo athletes (p<0.05), therefore, the bone mineral content (g) and Z-score were not significantly different between groups. The comparison of maximum torque values of knee extensors and flexors were not significantly different between groups (p>0.05). On the other hand, the muscular endurance evaluated with the fatigue index was significantly different between groups: higher fatigue index values were calculated for taekwondo athletes (p<0.05). In consequence, body composition differs according to the sport training, and this reflects to the maximum strength and muscular endurance performance.